2008
DOI: 10.3382/ps.2007-00411
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Dehydrated Pasture and Citrus Pulp on the Performance and Meat Quality of Broiler Chickens

Abstract: Some feedstuffs containing significant levels of fiber may be a good source of bioactive compounds that may contribute to improving broiler meat quality. However, high fiber level can have a negative impact on broiler performance. A study was undertaken to investigate the impact of incorporating citrus pulp (5 or 10%) or dehydrated pasture (5 or 10%) on the performance, carcass yield, and characteristics of broiler chickens. A diet containing neither citrus pulp nor dehydrated pasture was used as control. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
62
4
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(87 citation statements)
references
References 48 publications
19
62
4
2
Order By: Relevance
“…Meat fatty acid profile and cholesterol concentration are considered as the pivotal role in human diet as they have hypercholesterolemic properties, which are associated with coronary heart diseases (Daley et al, 2010), while dietary n-3 fatty acids including α-linolenic acid and its metabolites reduce the risk of heart disease (De Lorgeril et al, 1994). The increased concentrations of SFA (stearic acid) and UFA (myristoleic acid, α-linolenic acid, eicosatrienoic acid, arachidonic acid) in CPB dietary group (Table 8) supported the findings of Mourão et al (2008). They reported palmitic and stearic acids as the predominant fatty acids found in chicken meat as SFA, whereas linoleic and arachidonic acid as PUFA when supplied citrus byproduct in broiler diet.…”
Section: Fatty Acid Profilesupporting
confidence: 67%
See 1 more Smart Citation
“…Meat fatty acid profile and cholesterol concentration are considered as the pivotal role in human diet as they have hypercholesterolemic properties, which are associated with coronary heart diseases (Daley et al, 2010), while dietary n-3 fatty acids including α-linolenic acid and its metabolites reduce the risk of heart disease (De Lorgeril et al, 1994). The increased concentrations of SFA (stearic acid) and UFA (myristoleic acid, α-linolenic acid, eicosatrienoic acid, arachidonic acid) in CPB dietary group (Table 8) supported the findings of Mourão et al (2008). They reported palmitic and stearic acids as the predominant fatty acids found in chicken meat as SFA, whereas linoleic and arachidonic acid as PUFA when supplied citrus byproduct in broiler diet.…”
Section: Fatty Acid Profilesupporting
confidence: 67%
“…The increased concentration of total n-3 PUFA and the decreased ratio of n-6/n-3 in CPB dietary supplementation might have been due to the synergism of probiotic strains and CJ (Table 8). Supplementation of dietary citrus pulp increased meat PUFA concentration in broiler (Mourão et al, 2008). Paengkoum et al (2011) found a reduced ratio of n-6/n-3 fatty acid in meat when supplemented with Lactobacillus and Saccharomyces fermented feed in broilers and goats.…”
Section: Fatty Acid Profilementioning
confidence: 99%
“…We found that feeding lambs with the diet containing 35% DCP (CIT) increased the concentration of α-tocopherol in plasma (P < 0.05) and resulted in a twofold and threefold greater concentration of α-tocopherol in liver and in muscle, respectively (P < 0.05 and P < 0.01 for liver and muscle, respectively; Table 2). Mourão et al (2008) found that the inclusion of 5% or 10% DCP in the diets of broilers did not affect the concentration of α-tocopherol in muscle compared with a conventional cerealbased diet. To our knowledge, no information has been previously reported on the effect of feeding CP to ruminants on the vitamin E concentration in the tissues.…”
Section: +2mentioning
confidence: 88%
“…On the contrary, Chaudry et al (2004) have shown that chickens receiving citrus peel had similar feed consumption to the birds in CON group. Otherwise, the increased DFI of broilers has been observed after dietary inclusion of citrus pulp or DLP (Mourão et al 2008;Nobakht 2013). The lower DFI of chickens in our study might lead to reduced DWG and BW following supplementation with DLP.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Nobakht (2013) indicated that dried lemon pulp (DLP) improved growth performance of chickens across the entire production period. Moreover, citrus pulp was indicated to expand the gastrointestinal tract in broiler chickens (Mourão et al 2008). Nevertheless, effects of dried lemon pulp (DLP; citrus aurantifulia) on the morphology of small intestine and humoral immunity in broilers are less investigated.…”
Section: Introductionmentioning
confidence: 99%